Pkm Bagi Guru Smp Yang Mengalami Kesulitan Menggunakan Software Geogebra Dalam Pembelajaran Matematika - Yulianto Wasiran; Ibnu Maja; Farida Husien (Aptekmas Jurnal Pengabdian pada Masyarakat, 2019)
One reason is that the process of learning mathematics related to geometry is not yet optimal, it is the difficulty of the teacher to visualize abstract geometrical objects. Geogebra software can be used as a tool to construct, demonstrate or visualize abstract problems in learning geometry material. The problem faced by partners in implementing the geometry learning process by using Geogebra's assistance as a learning medium is the low knowledge of teachers in the use of Geogebra software and the low skills of teachers in using Geogebra software in learning geometry material. In an effort to overcome partner problems, the solution offered was to provide training and assistance to the Geogebra application to junior high school mathematics teachers in Banyuasin III to assist them in the process of learning mathematics. This activity includes theory, practice, and exercises given to participants so that skilled participants use Geogebra. This activity has succeeded in increasing teacher skills in knowledge and skills using Geogebra software for Mathematics learning. Participants understand the use of this software and are also skilled at using it for learning geometry material. This activity has also produced several instructional materials for Geogebra software assisted geometry materials.